2021
DOI: 10.1038/s41598-021-87290-z
|View full text |Cite
|
Sign up to set email alerts
|

The riddle of orange–red luminescence in Bismuth-doped silica glasses

Abstract: For over the past two decades it has been believed that the intense orange-red photoluminescence in Bismuth-doped materials originates from Bi$$^{2+}$$ 2 + ions. Based on the results from magnetic circular polarization experiments, we demonstrate that this hypothesis fails for Bismuth-doped silica glasses. Our findings contradict the generally accepte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 54 publications
2
5
0
Order By: Relevance
“…5,9 The first authors 9 did not report UV emission but instead observed some emission bands between 500–800 nm. These bands and similar ones in other systems, were subsequently associated with the spin–orbit 2 P 1/2 and 2 P 3/2 (1,2) levels of the 6s 2 6p configuration of Bi 2+ , 11–13 to Bi 3+ pairs or clusters, 9 charge transfer transitions, radiative decay of self-trapped excitons, 14,15 Bi 3+ -defect emission, bismuth-oxygen species, 6 and other sources. 16 Furthermore, near infrared (NIR) emission bands with millisecond or sub-millisecond lifetimes have been associated with Bi 0 and Bi + .…”
Section: Introductionsupporting
confidence: 54%
See 2 more Smart Citations
“…5,9 The first authors 9 did not report UV emission but instead observed some emission bands between 500–800 nm. These bands and similar ones in other systems, were subsequently associated with the spin–orbit 2 P 1/2 and 2 P 3/2 (1,2) levels of the 6s 2 6p configuration of Bi 2+ , 11–13 to Bi 3+ pairs or clusters, 9 charge transfer transitions, radiative decay of self-trapped excitons, 14,15 Bi 3+ -defect emission, bismuth-oxygen species, 6 and other sources. 16 Furthermore, near infrared (NIR) emission bands with millisecond or sub-millisecond lifetimes have been associated with Bi 0 and Bi + .…”
Section: Introductionsupporting
confidence: 54%
“…The reader is referred to reviews showing the current interest in bismuth species which not only present literature data but also comment upon the difficulties in spectral interpretation. 3,13,16,17,19,36,37 The elpasolite Cs 2 NaBiCl 6 crystallizes in the Fm3 ˉm space group at RT, with Na + and Bi 3+ ions each surrounded by six Cl − ions to form [NaCl 6 ] 5− and [BiCl 6 ] 3− octahedra, whereas Cs + ions are 12-coordinated (Fig. 1b).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Laguta et al. showed that the ground state of luminescence center was a magnetic singlet with effective spin of 0, proving that Bi 2+ was not the BAC in bismuth‐doped silica glass 43,44 . This finding is also supported by crystal field modeling 45 .…”
Section: What Are the “Bacs” In Bismuth‐doped Fiber?mentioning
confidence: 88%
“…In bismuth‐doped pure silica fibers, only Bi‐O‐Si linkages are expected to form 19 . The luminescence‐related bismuth species are identified as ions, serving as structural modifiers 20 . With phosphorous doping, Bi‐O‐P is also formed 21 .…”
Section: What Are the “Bacs” In Bismuth‐doped Fiber?mentioning
confidence: 99%